2015
DOI: 10.1038/pcan.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on management of acute urinary retention

Abstract: We recommend use of α1-adrenergic receptor blockers before TWOC and discourage emergency operative management. Use of SPC over IDC in AUR is debatable. Duration of catheterisation is controversial but <3 days is a safe option in avoiding catheterisation-related complications. Although TURP remains the current gold standard, there has been an emergence of newer operative management utilising laser techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…Management of UR secondary to BPO (UR/BPO) varies widely. Relevant systematic reviews (SRs) are scarce [19][20][21]. The European Association of Urology (EAU) Nonneurogenic Male Lower Urinary Tract Symptoms (LUTS) Guidelines Panel acknowledges the current lack of high certainty of evidence (CoE) and the growing scientific base, and cites the need to understand more about management options.…”
mentioning
confidence: 99%
“…Management of UR secondary to BPO (UR/BPO) varies widely. Relevant systematic reviews (SRs) are scarce [19][20][21]. The European Association of Urology (EAU) Nonneurogenic Male Lower Urinary Tract Symptoms (LUTS) Guidelines Panel acknowledges the current lack of high certainty of evidence (CoE) and the growing scientific base, and cites the need to understand more about management options.…”
mentioning
confidence: 99%
“…There is controversy surrounding the length of catheterisation time and its relationship with successful IDC removal. Five studies reviewed by Yoon et al (2015) revealed no consistency regarding timing and success. It was however noted that having an indwelling urinary catheter for greater than 3 days was affiliated with increased complication such as infection (Yoon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reviewed by Yoon et al (2015) revealed no consistency regarding timing and success. It was however noted that having an indwelling urinary catheter for greater than 3 days was affiliated with increased complication such as infection (Yoon et al, 2015). The rate of hospital acquired UTIs reported in our study were the same (12%) for both successful and unsuccessful IDC removals (p=0.99).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Acute urinary retention can be broadly classified as spontaneous AUR (sAUR), which mainly occurs secondary to the natural history of BPH, and precipitated AUR, which occurs in response to a surgical procedure involving general or loco-regional anesthesia, bladder over-distension, urinary tract infection, or medications with sympathomimetic or anticholinergic effects. 4,5 Age, severe LUTS, low maximum urine flow rate (Qmax), high post-void residual urine, huge prostate, and high serum PSA levels have been proposed as significant risk factors for sAUR. 3,6 Several studies have addressed the relationship between climatic parameters and BPH/LUTS symptoms.…”
Section: Introductionmentioning
confidence: 99%